2020
DOI: 10.3390/insects11020124
|View full text |Cite
|
Sign up to set email alerts
|

Propolis Consumption Reduces Nosema ceranae Infection of European Honey Bees (Apis mellifera)

Abstract: Nosema ceranae is a widespread obligate intracellular parasite of the ventriculus of many species of honey bee (Apis), including the Western honey bee Apis mellifera, in which it may lead to colony death. It can be controlled in A. mellifera by feeding the antibiotic fumagillin to a colony, though this product is toxic to humans and its use has now been banned in many countries, so in beekeeping, there exists a need for alternative and safe products effective against N. ceranae. Honeybees produce propolis from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 84 publications
1
45
0
Order By: Relevance
“…In several studies, essential oils such as mint ( Mentha pepper L.), melissa ( Melissa officinalis L.), coriandrum ( Coriander sativum L.), thyme ( Satureja hortensis L.) oils, other phytochemicals such as caffeine, clove oil, gallic acid, kaempferol and p-coumaric acid, and even propolis expanded honeybee longevity and to some extent, reduced nosemosis levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Such phytochemicals as clove oil, laurel extract and sulforaphane, moderately decreased Nosema -infection, but at the same time, strongly reduced honeybee lifespan [ 33 , 36 , 37 ]. Other tested phytochemicals, such as amygdalin, anabasine, aucubin, catalpol, nicotine and thymol, had no effect against Nosema infection [ 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, essential oils such as mint ( Mentha pepper L.), melissa ( Melissa officinalis L.), coriandrum ( Coriander sativum L.), thyme ( Satureja hortensis L.) oils, other phytochemicals such as caffeine, clove oil, gallic acid, kaempferol and p-coumaric acid, and even propolis expanded honeybee longevity and to some extent, reduced nosemosis levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Such phytochemicals as clove oil, laurel extract and sulforaphane, moderately decreased Nosema -infection, but at the same time, strongly reduced honeybee lifespan [ 33 , 36 , 37 ]. Other tested phytochemicals, such as amygdalin, anabasine, aucubin, catalpol, nicotine and thymol, had no effect against Nosema infection [ 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such phytochemicals as clove oil, laurel extract and sulforaphane, moderately decreased Nosema -infection, but at the same time, strongly reduced honeybee lifespan [ 33 , 36 , 37 ]. Other tested phytochemicals, such as amygdalin, anabasine, aucubin, catalpol, nicotine and thymol, had no effect against Nosema infection [ 33 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of an effective nosemosis suppressant, various compounds, e.g., essential oils and plant extracts, have been subjected to intensive research [40]. Additionally, propolis, produced from resinous substances collected from plants and used by bees to protect their nests from parasites and pathogens, is studied as an alternative to fumagillin [41,42]. Promising compounds for the treatment of nosemosis are porphyrins [43].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to self-medication effects, propolis components (e.g., ethanolic extracts) harvested from bees in Asia and Europe have been shown to lower mortality and Nosema infections in Asian honey bees (Apis cerana), dwarf honey bees, (Apis florea) and European honey bees (Yemor et al, 2015;Suwannapong et al, 2018;Mura et al, 2020). Recently, Arismendi et al (2018) reported that methanolic Chilean propolis extracts reduce N. ceranae loads and increase survival of European honey bees (A. mellifera).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Arismendi et al (2018) reported that methanolic Chilean propolis extracts reduce N. ceranae loads and increase survival of European honey bees (A. mellifera). Mura et al (2020) reported that ethanolic Spanish propolis extracts reduce N. ceranae loads in European honey bees and identified high concentrations of caffeic acid, ferulic acid, ellagic acid, and quercetin derivatives in their extracts. Bee species, extraction methods, and especially geographical origin of propolis all have an effect on its bioactivity, most likely on account of variations in chemical composition (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%